PENGARUH KINERJA LINGKUNGAN, KEPEMILIKAN SAHAM PUBLIK, PUBLIKASI CSR, UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Sulaeman Sarmo; I Dewa Gde Bisma; Muhdin Muhdin; Sarifuddin Sarifuddin (Universitas Muhammadiyah Jember, 2022)
This study aims to examine the effect of Environmental Performance, Public Share Ownership, CSR Publications, Company Size on Financial Performance (Case Study on Manufacturing Companies on the Indonesia Stock Exchange in 2017-2019). This type of research is associative research which aims to determine the relationship between two or more variables. The type of data used in this study is quantitative data using secondary data. The sampling technique used in this study was purposive sampling so that the number of samples used in this study was 117. While the data processing in this study was carried out using multiple regression using SPSS. The results of this study indicate that environmental performance, public share ownership, CSR publications and company size simultaneously have no effect on financial performance. Partially, public share ownership and CSR publications have an effect on financial performance. Environmental performance and company size have no effect on financial performance. The implication of this research is that for further research, financial performance should be used as a proxy for return on assets and for environmental performance variables using an index because there are indications that it has an effect on financial performance.